Preventive Maintenances of Waste Crushing Equipment at Subang State Polytechnic - Indra Indra; Adhan Efendi; Yohanes Sinung Nugroho (VANOS Journal of Mechanical Engineering Education, 2023)
The research in this final project aims to determine the preventive maintenance schedule for the plastic waste smelter and to determine the application of preventive maintenance to the plastic waste smelter. The maintenance process for this tool uses preventive maintenance with inspection, small repair, medium repair and overhaul (ISMO) methods. The implementation method of waste smelter into plastic involves data collection through direct observations of the smelter area, component identification, maintenance schedule planning, expert validation, and routine preventive maintenance execution. The research findings indicate that the systematic and scheduled application of maintenance effectively preserves the optimal performance of the smelter machine. These measures not only enhance operational efficiency but also reduce the risk of damages and potential downtime that could disrupt the production process, contributing to the sustainability and quality of plastic waste processing.